The Effect of Service Quality on Customer Satisfaction at the Laguna, a Luxury Collection Resort & Spa, Nusa Dua, Bali - Suryadi, Sherin Natasha Suryadi; Sulistyawati, Ni Luh Ketut Sri; Sabudi, I Nyoman Sukana (PT FORMOSA CENDEKIA GLOBAL, 2024)
Hotels to increase competitiveness need to prioritize customer satisfaction with the quality of service that affects. The study aims to determine the effect of service quality on customer satisfaction of The Laguna, a Luxury Collection Resort & Spa, Nusa Dua, Bali. The data used includes quantitative data in the form of questionnaires and qualitative data in the form of customer complaints and interviews with Human Resources Staff. The sampling technique method used in this research is purposive sampling. Analysis was carried out using simple linear regression and SPSS version 29 for Windows. This study gives results if Customer Quality (X) has a significant effect on Customer Satisfaction (Y) with a tcount> ttable = 16.010> 1.661 and a significance number < α = 0.000 < 0.05. This study concludes that service quality has a significant effect on customer satisfaction.